Economic Implications of Energy Security in the Short Run - Šumskis, Vaidotas; Giedraitis, Vincentas (Ekonomika, 2015)
Energy security is one of the primary goals of the European Union energy policy as the region relies mostly on imports to meet its energy resources demand. In 2013, the share of the net imported energy resources was as high as 54.5% of total energy consumption in the 28 member states of the European Union. Research on energy security involves a detailed analysis of economic, technological, and socio-political factors. The main objective of this study is to find out the economic consequences in the short run due to changes in the level of the security of energy resources supply. In order to acquire quantitative measures of the research object, the energy security index calculation methodology proposed by Jansen et al. (2004) is applied. To explore what effects, if any, energy security has on the economy of the EU, five economic indicators, with which the probable short-term impact of energy security is the most likely, are distinguished: real GDP, inflation, current account balance, foreign direct investment, and employment. Granger causality tests of the panel VAR model reveal that in the short run employment may be negatively affected by energy security. The effect itself is relatively small and short-lived. No short term causality is observed running from energy security towards the remaining macroeconomic variables of the panel VAR model. Such conclusions would suggest making the European Union energy policy decisions without prioritizing possible swings of the energy security level in the short run.
Keywords: energy security; panel VAR; Granger causality; energy policy